Implementing Self Access Material for Promoting Learner Autonomy In Teaching ESP - Kuswanto, Welly (ELLITE, 2016)
This research used qualitative research design. Fraenkel and Wallen (2006) define qualitative research as documenting or portraying the everyday experience of individuals by observing and interviewing them. In this case, the researcher interviewed, observed teaching and learning ESP process and documentation by collecting document needed. Finally, Teacher as facilitator is easy to develop learners autonomy in teaching ESP by utilizing Self Access Material in form of providing relevant videos, providing software and online sources, producing in-house material development, making authentic podcasts accessible, promoting CALL, turning workshop recordings into self-access activities and using authentic music resources. By fostering self access material and implement it by using nine strategies namely setting objectives, selection of materials, methods, teacher’s role, teacher-learner relationship, learning environment, homework, presentation and talks and evaluation, teacher is able to trigger the learners to develop the ESP materials given.Keywords: Learner autonomy, self access material, ESP.